1999
DOI: 10.1111/j.1574-6968.1999.tb08851.x
|View full text |Cite
|
Sign up to set email alerts
|

Trophozoites ofGiardia lambliamay have a Golgi-like structure

Abstract: Trophozoites of the primitive protozoan Giardia lamblia have been considered as cells which do not present the Golgi complex. Using C(6)-NBD ceramide, which has been shown to label the Golgi complex of mammalian cells, labelling of the perinuclear region of G. lamblia was observed by confocal laser scanning microscopy. Transmission electron microscopy of thin sections and of replicas of freeze-fractured cells revealed the presence of concentric perinuclear membranes resembling the Golgi complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The diplomonads as the most basal eukaryotes known to date may shed light on some of these developments. For example, certain groups suggested that Giardia has no membrane structures resembling a Golgi apparatus, whereas others have claimed to detect the classical multicisternal membrane arrangement in EM studies (25,43). In agreement with the former, we recently showed that sorting of cargo proteins to the regulated ESV or the constitutive VSP pathways occurred at or immediately after export from the ER during encystation (18).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The diplomonads as the most basal eukaryotes known to date may shed light on some of these developments. For example, certain groups suggested that Giardia has no membrane structures resembling a Golgi apparatus, whereas others have claimed to detect the classical multicisternal membrane arrangement in EM studies (25,43). In agreement with the former, we recently showed that sorting of cargo proteins to the regulated ESV or the constitutive VSP pathways occurred at or immediately after export from the ER during encystation (18).…”
Section: Discussionsupporting
confidence: 71%
“…In a tEM survey using a novel method for preparing adhering Giardia for analysis we found no evidence for conventional Golgi stacks in a single parasite. Most encysting cells contained a large spindle-shaped membrane structure (up to 2 m) adjacent to one or both nuclei that had been interpreted as Golgi stacks in earlier EM investigations of randomly sectioned cells (43), but resembled "karmellae" from higher eukaryotes (i.e. layers of proliferated ER membranes wrapped around the nucleus (44)).…”
Section: Discussionmentioning
confidence: 99%
“…Possibly in these cases, the CWP2 basic extension competes with endogenous CWP2 for an anionic receptor. Localization of T CWP2 -HA and VSPH7(ϪTMϩT CWP2 )-HA moved from the ER to a more limited clamp-shaped pattern adjacent to the ER/nuclear envelope compartment, in a pattern similar to the Golgispecific marker 12-(N-methyl-N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl))-ceramide (3,41). In these experiments, the presence of the basic extension inhibited extracellular secretion of chimeras containing the CWP2 basic extension.…”
Section: Discussionmentioning
confidence: 97%
“…As the majority of ceramide is taken up from the culture medium or from the small intestinal milieu, some could be generated by breaking down sphingomyelin by Smase enzymes [38•, 4547]. Exogenously administered fluorescently conjugated ceramide was found to be targeted in the ER/perinuclear regions of trophozoites [48, 49], and in encysting cells it reacted with parallel perinuclear cisternae, which appeared to be a Golgi apparatus [25, 35, 36, 50]. This suggests that exogenous ceramide not only serves as a precursor of GlcCer but is also required for organelle biogenesis in Giardia.…”
Section: Sphingolipids and Encystationmentioning
confidence: 99%